Penguatan Profesionalitas Guru BK melalui Pengembangan Pribadi Konselor dalam Praktik Layanan Konseling di SMA: Studi Kualitatif - Mariana Astuti; Latif Hamidi; Baiq Mahyatun; Indah Sofianita; Yuliana Eka Safitri; Silmi Rostiana; Rizkia Maulida; Sridewi Supriyani; Muzayyin Fanani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Guidance and Counseling (BK) teachers' professionalism is a key element in ensuring the quality of school counseling services. Alongside pedagogical and technical competencies, the counselor’s personal development plays a strategic role in establishing therapeutic relationship effectiveness. This study aims to explore the reinforcement of BK teachers' professionalism through the counselor's personal development in high school counseling practices. Utilizing a qualitative approach with a single-case study design, this research involved a BK teacher at SMAN 3 Selong, purposively selected based on over 15 years of experience and a track record as a national instructor. Data were gathered through in-depth interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model. The results reveal that professionalism reinforcement based on personal development manifests in four primary processes: (1) self-reflection on handling critical cases, (2) managing student emotions through integrating coaching techniques and the restitution triangle, (3) independent competency development by designing assessment instrument applications, and (4) internalizing professional ethics and multi-directional interpersonal communication. This process significantly enhances emotional maturity, interpersonal competence, active listening skills, and professional courage in mediating. This study recommends integrating personal approach training and micro-counseling techniques during undergraduate studies.